The fitting of the norms of operation and interaction in the Instagram with its structure - mostafa ghanizadeh; ali yousefi; gholamreza sedigh ouraee (مطالعات رسانه‌های نوین, 2020)
Instagram is a photo-oriented social network that has gained popularity amongst Iranians in recent years. The norms of action and interaction in this social network have their own characteristics, which vary in normal interaction. difference is due to the nature of the online social network and its specific structure. The structure in the space of the Instagram is the parts that are designed by the operators, which creates the possibilities for action and creates constraints for it. to discover these differences, in this paper, the norms of action and interaction are described. for this description, the method of nethnography has been used. To ensure the authenticity of norms that discovered by the researcher, an online questionnaire has been set up and completed by 110 people. Finally, with the help of Raymond Boudon's methodology , the structure , norms , practices , and social interaction in this social network have been discussed.